Are the Rural Electrification Efforts in the Ecuadorian Amazon Sustainable? - Cordero-Carrasco, R (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
In this paper, we assess the sustainability of rural electrification programs in Ecuador, paying special attention to programs targeting small indigenous communities in the Amazon basin. Our assessment considers four dimensions of sustainability (institutional, economic, environmental, and socio-cultural) and is based on an exhaustive qualitative document analysis, complemented by semi-structured expert interviews. We found that disruptive changes have affected the electrification policies in Ecuador during decades of avoiding the development of strengthened institutions. Despite this major drawback, we found that there is a consensus on granting access to energy for all. This partially explains the national efforts, persistent through different administrations to fund rural electrification. However, in the case of off-grid photovoltaic solutions, these efforts have consistently neglected allocating funds for operation and maintenance, which has seriously compromised the sustainability. Moreover, although Ecuadorian officials declared to favor stand-alone photovoltaic systems in the case of indigenous communities in the Amazon, we found that environmental or socio-cultural aspects have a minor role in the selection of these systems. Progress regarding environmental awareness, social acceptance, and cultural justice, is still needed for ensuring the sustainability of rural electrification efforts in the Ecuadorian Amazon. © 2016 by the authors; licensee MDPI, Basel, Switzerland.